Long‐term benzodiazepines and z‐drug prescribing in Australian general practice between 2011 and 2018: A national study. Issue 1 (17th December 2021) - Woods, Amelia; Begum, Mumtaz; Gonzalez‐Chica, David; Bernardo, Carla; Hoon, Elizabeth; Stocks, Nigel
Abstract: Despite reducing benzodiazepine prescribing, benzodiazepine‐involving deaths have substantially increased in Australia. This study aimed to explore patterns in long‐term prescribing of medications (benzodiazepine and z‐drugs [BZD]) used for sleep‐issues/insomnia in Australia to better understand these changes. Open cohort study using de‐identified electronic health records of 1 414 593 adult patients regularly attending 404 Australian general practices from 2011 to 2018 (MedicineInsight). We used logistic regression adjusted for patient and practice characteristics to; (1) estimate long‐term BZD prescribing prevalence (≥3 prescriptions in 6 months) and the associated sociodemographic factors, and (2) Poisson regression to compute annual changes in prescribing rates. Long‐term BZD prescribing changed from 4.4% in 2011 to 5.8% in 2015, remaining relatively stable until 2018 (annual increase +2.5% [95% CI +2.0%;+3.0%]). Long‐term BZD prescribing in any year was up to six times more likely in elderly rather than in younger patients and 30%–43% more prevalent in females, or patients living in or attending a practice located in more disadvantaged areas. The increase was more pronounced among males, adults aged 35–49 years, and individuals living in advantaged areas. The median duration among incident cases decreased from 1183 to 322 days between 2011 and 2017, and was up to 197 days longer among elderly females than males. Despite a slight increase and recent stability in long‐term BZD prescribing, the higher rates and durations among elderly patients, women, or those living in more disadvantaged areas are concerning and highlights the need for interventions that reduce the potential harms of long‐term BZD use in vulnerable groups. Abstract : Long‐term prescribing of BZD's in Australian general practice increased in the initial years of our study and more recently showed an apparent plateau Nonetheless, the median duration of these episodes (322 days in 2017) is still 11 times higher than current recommendations. These findings coincide with a higher number of hospitalisations and deaths associated with BZD use in Australia, despite an overall decline in their prescribing.